THE WRITING SKILL STIMULATION OF CHILDREN AGED 5-6 YEARS - Adriani Rahma Pudyaningtyas; Nurul Kusuma Dewi; Hana Tiara Pertiwi (Universitas Muhammadiyah Ponorogo, 2019)
The purpose of this research was examined the implementation of writing skill stimulation at TK Negeri Pembina Manahan Surakarta. The research used a qualitative approach with ethnomethodology study. The subject of research were teachers and children aged 5-6 years. The data collecting techniques used interview, observation, and documentation. The techniques for testing the data validity by triangulation of technique and source. The data analysis technique used the interactive data model by Milles and Huberman.The research result showed that TK Negeri Pembina Manahan did the writing skill stimulation through the learning activity based on the Early Childhood Education Curriculum of 2013. The stimulation did through writing activity and writing skill reinforcement activity (drawing, coloring, and cutting). The thematic learning with scientific approach supports the varied writing skill stimulation. These activities are able to support the children’development of writing skill, including: (1) the children are able to grip the pencil; (2) writing the self-name; and (3) writing word and number.